The The Role of Cultural Parks in Strengthening Performance Arts-Based Cultural Tourism to Support Sustainable Tourism - I Wayan Kusuma Di Biagi; Rapi Renda; Muhammad Kholid Arif Rozaq; Galih Suryadmaja; Nandi Arfian Halil (Borong Newinera Publisher, 2026)
This study examines the role of the Cultural Park in strengthening performance arts-based cultural tourism in West Nusa Tenggara (NTB) to support sustainable tourism. Although NTB possesses rich natural and cultural resources, the integration of performing arts into tourism development has not yet been optimized. Therefore, this research focuses on two main issues: (1) the extent to which the Cultural Park maximizes its potential as a driver of performance arts-based cultural tourism in NTB; and (2) its role in supporting sustainable tourism development. This study employs a descriptive qualitative method involving stages of data collection, analysis, and reporting. Data were obtained through observation, interviews, and document studies, and were analyzed inductively. The analysis applies the 6A tourism development model (Attraction, Accessibility, Amenities, Accommodation, Activities, Ancillary Services). The research also aligns with Asta Cita of the President, point 3 in the RPJMN 2025–2029, with a target achievement of Technology Readiness Level 3 (TRL 3) and SDGs indicator point 8. The findings reveal that NTB Cultural Park has strengths in the diversity of traditional and contemporary arts, the availability of performance facilities, and its function as a center for cultural interaction. However, limitations in curation, digital promotion, cultural calendars, and cross-sector integration remain challenges. Socially, the Cultural Park contributes to preserving cultural identity and empowering art communities; economically, it fosters the creative economy and job opportunities; and ecologically, it strengthens local wisdom in line with sustainability principles.